The paths from walk preference to walk behavior: Applying latent factors in structural equation modeling - Coogan, Matthew A.; Adler, Thomas; Karash, Karla (Journal of Transport and Land Use, 2012)
A structural regression model has been developed to explore the relationship among key factors in the explanation of utilitarian walking. The model examines the relationship between and among unobserved, or ‘latent’ factors that reflect 1) the values and preferences operant at the time of residential selection; 2) the urban form of the neighborhood; 3) the urban form of the residence; 4) the level of auto dependency; and 5) the extent to which the neighborhood is found satisfactory by the participant and those whose opinions he/she respects. The model allows the detailed examination of the paths from initial inclination towards a neighborhood with walkable destinations, through a series of mediating unobserved factors, each of which might either impede or facilitate the adoption of utilitarian walking. Variations on the model allow for the examination of the role of attitudes and preferences towards suburban house formats separately from the question of walkable destinations, reflecting the possibility of a value conflict situation. Analysis of the model results can shed some light on the relationship between attitudes and values brought to bear at the time of residential selection, and the need to deal with conditions and constraints to walking associated with the built environment closer to the time of the walking decision.